Pemanfaatan Aplikasi Untuk Bisnis Online Bagi Kaum Perempuan di Desa Cemaga Tengah Kecamatan Bunguran Selatan Kabupaten Natuna - Sapariah Sapariah; Sri Wahyuni; Nanik Rahmawati (Jurnal Hawa : Studi Pengarus Utamaan Gender dan Anak, 2023)
This study aims to find out the reasons why women in Cemaga Tengah Village choose to do business online. The method used in this research is a qualitative method with a descriptive method approach. The data sources used are data sources in the form of observations, interviews and documentation. The data obtained through the results of semi-structured interviews. In this study to determine informants using purposive sampling technique or first determine the criteria of informants. The theory used in this research is Structural Theory from Anthony Giddens which talks about Agents and Structures where the agent is an actor or a woman who makes a change by utilizing structures or resources that exist inside and outside of an agent, namely through social business practices. on line. Based on the results of the analysis, the researchers found that the reasons for women doing business online were because of socioeconomic conditions, increasing relationships, and flexible work. Technology has many positive impacts on women. Technology is a resource for women to make changes in society. Online business has an impact on increasing socioeconomic conditions, social status, and also relationships. In addition to the positive impacts, there are also negative impacts, namely losses.